2018
DOI: 10.5546/aap.2018.eng.328
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of masked hypertension among children with risk factors for arterial hypertension

Abstract: The prevalence of MH in children with risk factors for arterial hypertension was close to 10%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…In mixed cohorts of patients with different risk factors for MH, the prevalence of MH ranged from 8 to 11% [ 2 , 69 ]. The prevalence of MH in children with several risk factors for hypertension has been studied recently [ 69 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In mixed cohorts of patients with different risk factors for MH, the prevalence of MH ranged from 8 to 11% [ 2 , 69 ]. The prevalence of MH in children with several risk factors for hypertension has been studied recently [ 69 ].…”
Section: Introductionmentioning
confidence: 99%
“…In mixed cohorts of patients with different risk factors for MH, the prevalence of MH ranged from 8 to 11% [ 2 , 69 ]. The prevalence of MH in children with several risk factors for hypertension has been studied recently [ 69 ]. Iturzaeta et al found MH in 9% of children in a prospective study among more than 100 children with at least one risk factor for hypertension such as prematurity, low birthweight, history of umbilical cord cannulation, isolated transient high OBP in the past medical history, overweight/obesity, diabetes, chronic kidney disease, or positive family history of hypertension [ 69 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation